Survei kecacingan pada anak dengan riwayat alergi di SD Negeri Talawaan Bajo Kecamatan Wori Kabupaten Minahasa Utara - Tuda, Aprilia E. J.; Wahongan, Greta J. P.; Pijoh, Victor D. (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2018)
Background: Helminthic infection is global health problem and often found in developing country with tropical and subtropical climate, especially Indonesia. There are several studies show the relation between helminthic infection and allergy. Aim: The purpose of this study is to see the helminthic infection survey in students with allergy history at Talawaan Bajo Public Elementary School in Wori District, North Minahasa Regency. Method: This study is a cross sectional descriptive study. Results: Interview using ISAAC questionnaire to identify the students with allergy history. Faeces and blood obtained from 22 students as sample. From 22 faeces samples, it was found that 2 (9.09%) samples are positive to helminthic infection, each of them caused by Trichuris trichiura and Ascaris lumbricoides. From two samples that are positive to helminthic infection, oneÂ  (50%) sample is eosinophilia.Conclusion: helminthic infection survey in students with allergy history at Talawaan Bajo Public Elementary School in Wori District North Minahasa Regency found two children with allergy history who suffer helminthic infection from 22 samples in total.